Asuhan Keperawatan Jiwa Pada Ny.M Dengan Masalah Utama Gangguan Persepsi Sensori : Halusinasi Penglihatan Akibat Skizofrenia Typemanik Di Ruang Dewaruci RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Dian Savitri; Slamet Wijaya B; Esti Nur Janah (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Health is one of the things that is very valuable in life so that community participation is needed to be able to improve the degree of health, as well as mental health which is still a significant problem in the world, including in Indonesia. Mental health is a condition in which an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can handle pressure, can work productively and is able to contribute to his community (Retno, 2020).